Effects of Catalase on Growth Performance, Antioxidant Capacity, Intestinal Morphology, and Microbial Composition in Yellow Broilers - Tang, Minghong; Fang, Rejun; Xue, Junjing; Yang, Kaili; Lu, Yi (Frontiers in Veterinary Science, 2022)
The objective of this experiment was to study the effects of catalase (CAT) on growth performance, antioxidant capacity, intestinal morphology, and microbial composition of yellow broilers. Male Lingnan yellow broilers (360), aged 1 day, were randomly divided into control group (CON) (fed with a basic diet), R1 group (fed with basic diet + 150 U/kg catalase), and R2 group (fed with basic diet + 200 U/kg catalase). Each group had 8 replicates and 15 chickens in each replicate. The test is divided into the early stage (1–30 days) and the later stage (31–60 days). The results showed that compared with the control group, groups R1 and R2 significantly (p < 0.05) increased the weight gain and reduced (p < 0.05) the ratio of feed to gain in the early and the whole stages; prominently increased (p < 0.05) the concentration of total antioxidant capacity (T-AOC), the activities of CAT, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) in livers, the activities of CAT and GSH-Px in serum, and CAT in the jejunum in the early and the later stages; markedly increased (p < 0.05) the villus height and the ratio of villus height to crypt depth of the duodenum in the early and the later stages, the villus height and the villus height:crypt depth ratio of the jejunum and ileum in the early stage, and significantly lowered (p < 0.05) the crypt depth of the duodenum (in the early and the later stages), jejunum, and ileum (in early stage); memorably (p < 0.05) increased the number of total bacteria and Bacteroidetes in ceca, as well as the number of Lactobacillus in the jejunum (p < 0.05) on the 30th; significantly (p < 0.05) increased the mRNA expression of junction adhesion molecule 2 (JAM2), mucin 2 (MCU2), and occlusal protein (occludin) in the duodenum in the early stage, and increased (p < 0.05) the mRNA expression of JAM2 in the jejunum in the later stage. Collectively, adding catalase (CAT) to the diet of yellow broilers can improve the growth performance and the antioxidant capacity, promoting the integrity of intestinal morphology, optimizing the composition of intestinal microorganisms, and upregulating the mRNA expression of tight junction protein.